p38 MAPK as a gatekeeper of reprogramming in mouse migratory primordial germ cells - Okamura, Daiji; Kohara, Aoi; Chigi, Yuta; Katayama, Tomoka; Sharif, Jafar; Wu, Jun; Ito-Matsuoka, Yumi; Matsui, Yasuhisa (Frontiers in Cell and Developmental Biology, 2024)
Mammalian germ cells are derived from primordial germ cells (PGCs) and ensure species continuity through generations. Unlike irreversible committed mature germ cells, migratory PGCs exhibit a latent pluripotency characterized by the ability to derive embryonic germ cells (EGCs) and form teratoma. Here, we show that inhibition of p38 mitogen-activated protein kinase (MAPK) by chemical compounds in mouse migratory PGCs enables derivation of chemically induced Embryonic Germ-like Cells (cEGLCs) that do not require conventional growth factors like LIF and FGF2/Activin-A, and possess unique naïve pluripotent-like characteristics with epiblast features and chimera formation potential. Furthermore, cEGLCs are regulated by a unique PI3K-Akt signaling pathway, distinct from conventional naïve pluripotent stem cells described previously. Consistent with this notion, we show by performing ex vivo analysis that inhibition of p38 MAPK in organ culture supports the survival and proliferation of PGCs and also potentially reprograms PGCs to acquire indefinite proliferative capabilities, marking these cells as putative teratoma-producing cells. These findings highlight the utility of our ex vivo model in mimicking in vivo teratoma formation, thereby providing valuable insights into the cellular mechanisms underlying tumorigenesis. Taken together, our research underscores a key role of p38 MAPK in germ cell development, maintaining proper cell fate by preventing unscheduled pluripotency and teratoma formation with a balance between proliferation and differentiation.